Potential of Fish Scales in the Eco-friendly Treatment of Fish Processing Industry Effluent - Devasena, Subhashree; Padmavathy, P.; Manimekalai, D.; Jeya Shakila, R. (Fishery Technology, 2023)
The discharge of effluent from seafood processing units is loaded with several organic and inorganic contaminants. This results in the deterioration of water quality and leads to water pollution in water bodies where effluents are discharged. Huge quantities of fish scales are discarded as solid waste from fish markets. In the present study, fish scales were utilized as potential adsorbent and tested for their adsorption ability in the treatment of fish processing industry effluent. The prepared adsorbent caused a significant reduction (p<0.05) (>50 %) in the concentration of alkalinity and hardness in the treated effluent. The concentration of Total solids (TS), Total Dissolved Solids (TDS), and Total Suspended Solids (TSS) showed significant (p<0.05) reduction (30-60 %) after treatment. Based on the results, the best adsorbent dosage and contact time for the most effective treatment of all parameters was observed to be 1 g/100 mL and 180 minutes. The porous surface and functional groups of adsorbent were characterized before and after treatment. The results of the present study revealed that fish scale adsorbent can be effectively used for the treatment of excess alkalinity and hardness in the effluent.